2011
DOI: 10.1007/s00436-011-2738-0
|View full text |Cite
|
Sign up to set email alerts
|

Essential oil composition and larvicidal activity of Saussurea lappa roots against the mosquito Aedes albopictus (Diptera: Culicidae)

Abstract: In recent years, uses of environment friendly and biodegradable natural insecticides of plant origin have received renewed attention as agents for vector control. The aim of this research was to determine larvicidal activity of the essential oil derived from roots of Saussurea lappa (Compositae) and the isolated constituents against the larvae of the Culicidae mosquito Aedes albopictus. Essential oil of S. lappa roots was obtained by hydrodistillation and analyzed by gas chromatography (GC) and GC-mass spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 32 publications
5
54
0
Order By: Relevance
“…Costunolide exhibited strong larvicidal activity against A. albopictus (Liu et al, 2011b). It also reported that, costunolide is involved to inhibit the expression of inducible nitric oxide synthase (De Marino et al, 2005;Fukuda et al, 2001;Matsuda et al, 2000;Park et al, 1996) and the DNA-binding activity of NF-κB (Castro et al, 2000;Koo et al, 2001;Stefani et al, 2006) and has potential as natural herbicide (Macias et al, 1999).…”
Section: Biological Functionsmentioning
confidence: 94%
“…Costunolide exhibited strong larvicidal activity against A. albopictus (Liu et al, 2011b). It also reported that, costunolide is involved to inhibit the expression of inducible nitric oxide synthase (De Marino et al, 2005;Fukuda et al, 2001;Matsuda et al, 2000;Park et al, 1996) and the DNA-binding activity of NF-κB (Castro et al, 2000;Koo et al, 2001;Stefani et al, 2006) and has potential as natural herbicide (Macias et al, 1999).…”
Section: Biological Functionsmentioning
confidence: 94%
“…Even today, scientists and the general public recognize their value as a source of new and complimentary medicines owing to their versatile applications [1] . Medicinal plants have been used for centuries as remedies for human diseases and offer a new source of biologically active chemical compounds as antimicrobial agents.…”
Section: Introductionmentioning
confidence: 99%
“…Curcuma longa, A. absinthium and S. lappa are commonly known as Haldi, Afsantheen and Kust, respectively in Pakistan. These herbs are enriched in biological active chemicals like C. longa, A. absinthium and S. lappa reported for curcumin, thujone and germacra-1,4,11-trien-12-oic acid, respectively (de Kraker et al, 2011;Liu et al, 2012;Riahi et al, 2013). Sporulation inhibition is a common criterion to assess the anticoccidial properties (Molan et al, 2009).…”
Section: Discussionmentioning
confidence: 99%